2018
DOI: 10.1111/evj.12824
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for osteochondrosis in various horse breeds

Abstract: Osteochondrosis (OC) is an injury to cartilage canals with a following necrosis in the growth cartilage, from there it can develop to osteochondrosis dissecans (OCD). Due to its high impact in the equine industry, new insights into predisposing factors and potential high-risk genetic variants are warranted. This article reviews advancements in quantitative and molecular genetics in refining estimation of genetic parameters and identifying predisposing genetic loci. Heritabilities were highest for hock OC with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…Most authors agree that some degree of motion disturbance is involved in the development of osteochondrosis/OCD . Clinical signs of these lesions become more evident in young horses with increased training and may lead to a decrease in their performance . Studies have shown that osteochondrosis in young horses affects the growing cartilage of the articular/epiphyseal complex of predisposed joints .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most authors agree that some degree of motion disturbance is involved in the development of osteochondrosis/OCD . Clinical signs of these lesions become more evident in young horses with increased training and may lead to a decrease in their performance . Studies have shown that osteochondrosis in young horses affects the growing cartilage of the articular/epiphyseal complex of predisposed joints .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs of these lesions become more evident in young horses with increased training and may lead to a decrease in their performance . Studies have shown that osteochondrosis in young horses affects the growing cartilage of the articular/epiphyseal complex of predisposed joints . The abnormal cartilage can be thickened, collapsed, or fragmented, and may progress to a separated osteochondral flap at specific predilection sites .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite earlier hopes that 'the OC gene(s)' would be found, there is now consensus that the genetic basis of OC is polygenic and highly complex. The review by Naccache et al [10] in this issue of EVJ describes quantitative trait loci (QTLs) shown to be significantly linked to OC in genome-wide studies on not less than 20 of the 33 chromosomes of the horse. A further complicating and most likely related issue is that the genetic contributors to OC may vary with OC at different locations and even in different manifestations of OC at the same location [11].…”
mentioning
confidence: 99%
“…It is a complex multifactorial orthopaedic condition that has been extensively reported, but the genetics are still far from being completely understood. The article by Naccahe, Metzger and Distl considers the current position of genetic and genomic knowledge by reviewing the quantitative and molecular genetics involved . They feel that gene expression may be helpful to understand pathophysiological processes in OC and to connect OC‐associated genomic regions with potential candidate genes.…”
mentioning
confidence: 99%